Cross-Age Peer E-Mentoring to Support Social Media Use: A New Focus for Intervention Research. (May 2019) - Grace, Emma; Raghavendra, Parimala
Young people who use augmentative and alternative communication (AAC) can experience reduced social participation and continue to face challenges in developing and using communication and literacy skills for real-life contexts. Drawing on emerging research, this discussion article highlights the potential benefits and advantages of participation in online conversations with peers as an additional support to both communication development and social participation for this group. Cross-Age peer e-mentoring to support participation in social media is proposed as a potential intervention strategy to enhance social participation and at the same time improve communicative competence and literacy for young people who use AAC.